Does super deduction R&D ï¬nancial policy in the pandemic Covid-19 give a super reaction? - Sari, Cahyani Tunggal; Estuti, Eni Puji; Indriastuti, Ariyani (Journal of Business & Banking, 2022)
This research was motivated by the announcement of the super deduction R&D ï¬nan- cial policy (PMK 153/2020) issued by the Indonesian government during the Covid-19 in 2020. This study tried to test and empirically prove either the presence or absence of abnormal returns on the day around the announcement, before and after the announce- ment optimal portfolio of pharmaceutical and health sector stocks during the observation time around the announcement of the super deduction R&D ï¬nancial policy. This is a quantitative research with event study using hypothesis testing from one sample t-test and paired sample t-test. The results showed that there was 1 day of observation, which indicated an abnormal return around the announcement day. Overall, before and after being announced based on the results of the paired sample t-test, it did not show any abnormal returns. The highest optimal portfolio analysis is on stock of Darya Varia Laboratoria company which have a weighting of 40.86% and there are two stocks that are not optimal. This study shows that there is a reaction of market participants to pharmaceutical and health stocks on the announcement even though the reaction is very small. Based on the result, there is a need for information related to research and development activities of pharmaceutical and health companies for investors if they want to improve their stock performance.